THE INTERACTIVE ROLES OF ORGANIZATIONAL CULTURE AND ACCOUNTANT PROFESSIONALISM IN CLOUD ACCOUNTING ADOPTION: EXPLORATORY STUDY - Abdullah Hussein Jameel; Bassem Rashid Ali; Imad Nayef Turki (Scholar Express Journals, 2024)
The research explores the interactive role of organizational culture in the adoption of cloud accounting, taking into account the professional characteristics of accountants (PCAs). To achieve this purpose, the researchers depend on both the descriptive and analytical approaches in collecting and processing the practical aspect of the research. A questionniar was prepared to gather data which were processed using SPSS. The study found a significant correlation and impact between organizational culture and cloud accounting in Iraqi commercial banks. This indicates that organizational culture plays an important and effective role in the use of cloud accounting. The research recommended deepening awareness of the accountatnts ins using cloud accounting due to its ease of use and can achieve perceived benefits. It also recommended building trust in cloud accounting by search for effective means that contribute to improving the quality of performance
Keywords: Accountants; cloud accounting; cloud computing; professional characteristics